Penerapan Mobilisasi Dini terhadap Intensitas Nyeri pada Pasien Post Operasi di Ruang HCU Cempaka RSUD dr. Moewardi Surakarta - Navaline Aulia Hexendri; Eska Dwi Prajayanti; Isti Wulandari (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Surgery is an invasive medical procedure to diagnose or treat a disease, which causes pain. Postoperative pain is a common and frequent problem. Early mobilization is very important as a gradual return to the previous mobilization stage. Early mobilization is carried out in stages to reduce the intensity of pain felt by the patient by carrying out early ambulation in stages from the first 8 hours. Objective: To determine the results of implementing early mobilization to reduce pain intensity in post-operative patients at the Cempaka HCU, Regional General Hospital (RSUD) Dr. Moewardi Surakarta. Method: This type of research is descriptive research in the form of a case study. Involving 2 post-operative patients. The research instrument used the Numeric Rating Scale (NRS) questionnaire. Results: research shows that before implementing early mobilization on Mr. S, an NRS score of 8 (severe pain) was obtained, while for Mrs. S obtained an NRS score of 4, likewise for Mrs. Conclusion: After applying early mobilization for 3 consecutive days to Mr.S and Mrs.N, it can be concluded that there was a decrease in the level of pain in both patients.